2022
DOI: 10.3390/cancers14163928
|View full text |Cite
|
Sign up to set email alerts
|

Different Prognostic Values of Tumour and Nodal Response to Neoadjuvant Chemotherapy Depending on Subtypes of Inflammatory Breast Cancer, a 317 Patient-Study

Abstract: Inflammatory breast cancer (IBC) is a rare entity with a poor prognosis. We analysed the survival outcomes of patients with nonmetastatic IBC and the prognostic value of tumour or nodal responses to assess their individual prognostic impact across IBC subtypes. This retrospective multicentre study included patients diagnosed with IBC between 2010 and 2017 to account for advances in neoadjuvant systemic therapies and modern radiotherapy at seven oncology centres in France. Three hundred and seventeen patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The specific manifestation was that the morphology of the cancer cells was irregular, the whole cell was swollen, and the boundary was unclear. It could be observed that vacuoles appeared in the cytoplasm, and the nucleus was enlarged or showed deep staining and deformity ( 67 ). The cases diagnosed as pCR by postoperative histopathology have been confirmed by multiple studies ( 68 ), and their recurrence-free survival rate and overall survival rate are better than those of cases that have not achieved complete pathological remission.…”
Section: Microscopic Pathologymentioning
confidence: 99%
“…The specific manifestation was that the morphology of the cancer cells was irregular, the whole cell was swollen, and the boundary was unclear. It could be observed that vacuoles appeared in the cytoplasm, and the nucleus was enlarged or showed deep staining and deformity ( 67 ). The cases diagnosed as pCR by postoperative histopathology have been confirmed by multiple studies ( 68 ), and their recurrence-free survival rate and overall survival rate are better than those of cases that have not achieved complete pathological remission.…”
Section: Microscopic Pathologymentioning
confidence: 99%